Forever and a day [compact disc, unabridged] : a James Bond novel - Horowitz, Anthony, 1955-; Fleming, Ian, 1908-1964 (Harper Audio, 2018)
A spy is dead. A legend is born. This is how it all began. The explosive prequel to Casino Royale, from best selling author Anthony Horowitz.